Highlights of progress in silage conservation and future perspectives. (26th October 2017) - Wilkinson, J. M.; Rinne, M.
Abstract: Highlights of progress in the production of silage over the past 50 years include the introduction of improved hybrids of maize ( Zea mays L.), the forage harvester, the big baler, polyethylene covering for horizontal silos, stretch‐wrap film for bales and novel additives designed to improve the fermentation and aerobic stability of silage. The key biochemical pathways in the silage fermentation have been described together with the effects of microbial and chemical additives on fermentation and aerobic stability during the feed‐out phase. The significance of oxygen and water in silage fermentation has been quantified and efficacy of covering silos has been established, with recent progress in the development of oxygen barrier film. Future perspectives include improving food safety and animal health by increasing the hygienic quality of silage, reducing the environmental impact of silage by decreasing loss of nitrogen to soil and atmosphere, reducing methanogenesis in the rumen and increasing methane yield from silage as biofuel, and the use of silages as feedstocks for multiple end uses in biorefineries.